Recent advances in the management of tuberculosis - Khan, Muhammad Babar; Mashhood, Asher Ahmed; Qureishi, Shaukat Mehmood (Journal of Pakistan Association of Dermatologists, 2016)
The importance of tuberculosis in Pakistan and other underdeveloped countries cannot be over emphasized. Despite inclusion of BCG vaccination in the EPI program and availability of the anti-tuberculosis medicines at affordable prices, tuberculosis is still the number one cause of prolonged morbidity. The emergence of Human Immunodeficiency Virus and multidrug resistant tuberculosis has added another dimension to an already complicated situation of tuberculosis globally. In response, vigorous efforts have been made to stratify the patient population and streamline the treatment of various categories of tuberculosis patients.